SUBSTITUSI LABU KUNING TERHADAP KUALITAS KUE MANGKOK - Gustina, Lia; Elida, Elida; Holinesti, Rahmi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This study aimed to analyze the effect of substitution on pumpkin as much as 25% and 35% of material that used to the quality of cupcakes (volume, shape, color, aroma, texture, and flavor). The kind of this research is true experiments with a completely randomized design method as well as three repetitions with 4 panelists . The data has been obtained and tabulated in tables and performed Variant Analysis (ANOVA), if there are differences result it will be continued to the Duncan test. The results showed significant effect on the quality of the volume (expands), shape (bowl-shaped section with 3-4 split on the surface), color (light yellow), aroma (pumpkin) and flavors (pumpkin), but it does not affect the quality : texture (soft), texture (elasticity), texture (having large pores) and flavor (sweet) and the best value found on the substitution of 35% (X2).Keywords: Cupcakes, Yellow Pumpkin, substitution, Quality.